Durable Results with In Situ Graft Repair of Ruptured Salmonella Aneurysm in a Patient with Autoimmune Deficiency Syndrome - Thompson, Patrick C.; Wang, Lisa; Columbo, Jesse; Schanzer, Andres; Robinson, William P. (International Journal of Angiology, 2016)
We describe a case of a 42-year-old male patient with advanced autoimmune deficiency syndrome (AIDS) (CD4 count of 16 cells/mm3) found to have a ruptured infected infrarenal aortic aneurysm. Emergent in situ repair was performed with a Hemashield Dacron graft (Boston Scientific, Natick, MA). Aortic tissue cultures grew group D Salmonella. Patient was placed initially on intravenous ciprofloxacin followed by lifelong oral levofloxacin and trimethoprim. Over 2 years following repair, he remains asymptomatic, with repair intact and no recurrent infection. This case is the first reported successful long-term repair of a ruptured salmonella infected abdominal aortic aneurysm in the setting of advanced AIDS.
Keywords: abdominal aortic aneurysm; mycotic aneurysm; AIDS; infection; ruptured aneurysm; in situ repair; salmonella